The Accessory Spleen Is an Important Pitfall of 68Ga-DOTANOC PET/CT in the Workup for Pancreatic Neuroendocrine Neoplasm. Issue 2 (February 2017) - Rufini, Vittoria; Inzani, Frediano; Stefanelli, Antonella; Castaldi, Paola; Perotti, Germano; Cinquino, Annarita; Indovina, Luca; Rindi, Guido
Abstract : Objective: The aim of the study was to assess the value and potential pitfalls of 68 Ga-DOTANOC positron emission tomography/computed tomography (PET/CT) in patients with suspected pancreatic neuroendocrine neoplasms (pNEN). Methods: Consecutive patients referred for 68 Ga-DOTANOC PET/CT for suspected pNEN between May 1, 2011, and October 31, 2014, were retrospectively assessed. Scan data were compared with cytological/histological final diagnosis. Pancreatic neuroendocrine neoplasm detection rate was determined on per-patient and per-lesion basis. Maximum standardized uptake values of lesions were determined. Results: Fifty-eight patients with 65 lesions were enrolled. Twelve patients had nonconfirmed diagnosis; of these, 7 were positive and 5 negative at PET/CT. Of 46 patients with confirmed diagnosis, 36 had pNEN; of these, 33 were positive, 1 negative, and 2 nonevaluable at PET/CT. Ten patients had non-NE lesions, of which 8 were positive, 1 negative, and 1 nonevaluable at PET/CT. Of 48 patients with positive PET/CT, 8 proved to have non-NE lesions, of which 6 were intrapancreatic accessory spleen. No significant maximum standardized uptake values difference was found between pNEN and non-NE lesions. Conclusions: Intrapancreatic accessory spleen is an important pitfall in 68 Ga-DOTANOC PET/CT for suspected pNEN. Cytological/histological confirmation is mandatory before any surgical procedure is undertaken.